Analysis of Multiple Choice Questions as an Evaluation Tool for the end of Year Assessment (PAT) in the Subject of Indonesian History Class XI SMA - Syahroni, Muhammad; Nurhasanah, Ana; Putra, Arif Permana (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This study aims to determine the validity, reliability, level of difficulty, discriminating power, and the effectiveness of the multiple choice distractor as an evaluation tool for history subjects in class XI SMAN 2 Pandeglang. This research is quantitative and descriptive. Students of class XI B and D IPS at SMAN 2 Pandeglang were used as the research sample. Based on the results of the research on 30 year-end assessment questions (PAT) for Indonesian history class XI IPS SMAN 2 Pandeglang for the 2021/2022 academic year, there were 13 valid questions (43.3%) and 17 questions (56.7%) which invalid. The reliability score of 0.49 indicates that neither the questions nor the results are reliable. On discriminating power, 20 items (66.7%) fall into the weak category, 7 items (23.3%) fall into the sufficient category, 1 (one) item (3.3%) falls into the good category, 2 (two) items (6.7%) fall into the very weak category, and there are no items in the very good category. The index of difficulty shows that 4 (four) items or 13.3% are included in the easy category, 26 items or 86.7% are classified as difficult, and there are no items included in the very difficult category. On the effectiveness of the distractor, all items (30) have the effectiveness of the distractor with good criteria. The results of the validation by the expert lecturer on the study of the questions showed that 27 out of 30 items had fulfilled the suitability aspect of the items with indicators, 29 out of 30 items were in accordance with scientific principles, all items (30) had one answer key. Meanwhile, the results of the validation of the construction of the questions showed that all questions met the aspects of the rules for writing items. And, as many as 27 of the 30 items were stated to fulfill the language rules in writing the items.